The Role Of ‘Aisyiyah Recitation In Forming Sakeenah Family - Rasta Kurniawati Br. Pinem (Proceeding International Seminar of Islamic Studies, 2019)
: The recitation is one of ‘Aisyiyah's efforts that can provide benefits to the public even family. This is appropriate with the meaning of ‘Aisyiyah as a women's organization that is engaged in religious, social and society. The recitation of ‘Aisyiyah, amounting to seven thousand study units spread throughout Indonesia that consist of a variety on ages and diverse activities.There are many programs can be carried out in the implementation of recitation in Aisyiyah, including the enlightening study program (at-Tanwir) especially providing enlightenment for families. The Sakeenah Family material is very important in guidance to the Sakeenah family. The important aspects of sakeenah family a are: a. Fostering Spiritual Aspects, namely the power of submission and obedience to Allah, the urge to rely only on Allah. The good spirituality will bring a sense of peace,even the security and peace in the souls of each member. b. Feelings of spirituality can be reflected in the behavior of worship and mu'amalah, relationship with Allah, with humans and with the natural surroundings. c. Spiritual husband and wife coaching. d. Spiritual formation in children. Spiritual nuances in Muslim families.The study of 'Aisyiyah which has been programmed according to the sakeenah family concept material is expected to function the family well. The sakeenah family function that has been formulated in the Sakeenah Family Guidance is to function as religious formation, biological and reproductive functions, civilization, love, protection, social, education, economic, environmental preservation function, internalizing Islamic values and regeneration function.In order to establish a sakeenah family in accordance with the five basic aspects above, and the formation of a family in accordance with its function, the 'Aisyiyah recitation method developed is adjusted to the congregation's conditions, including if the study participants are homogeneous (leaders, employees, young, old) can be done with training methods, workshops or out bond. However, if the participants are heterogeneous, the lecture, question and answer method, or listening methods can be used. Another method is the electronic media method, such as LCD and OHP. Then once a time can be made rihlah program or religious tourism, it can also do tadabur nature or a visit to a historic place or a comparative study program called Silaturrahim ‘Aisyiyah to other areas.